Continuous Exposure to Microplastics Does Not Cause Physiological Effects in the Cultivated Mussel Perna perna - Santana, Marina F. M.; Moreira, Fabiana T.; Pereira, Camilo D. S.; Abessa, Denis M. S. [UNESP]; Turra, Alexander (Springer Nature, 2018)
The environmental impact of microplastics is a challenging theme, especially under realistic experimental conditions. We investigated physiological responses to 0.1–1.0 μm PVC particles intake by the mussel Perna perna after a relative long-term exposure (90 days) at a less extreme concentration compared with previous studies (0.125 g/L). Microplastic intake was inferred by the presence of PVC in the feces of mussels, and physiological damages were assessed through ingestion rate, assimilation efficiency, growth rate, cellular and molecular biomarkers (lysosomal integrity, lipid peroxidation, and DNA damage), and condition index. All physiological responses showed nonsignificant effects of the microplastics on the exposed mussels. We suggest that, despite the experimental concentration of microplastics, mussels were able to acclimate to the exposure through their abilities for long-term recovery and tolerance to stresses. These data have positive implications for environmental health and in terms of human food resource because mussel farming is a worldwide practice that heavily relies on plastic materials, increasing the chances of microplastic exposure and mussels contamination.